Effect of magnetic field on the behavior of Electrochemical oxidation of Aluminum in 3.5% NaCl solution - Surya Darma; Hamdan Akbar Notonegoro; Naila Mubarok; Sukarno Sukarno; Bambang Soegijono (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
An irreversible electrochemical reaction from material interaction with the environment and causing degradation is known as corrosion. The electrolyte changes significantly affect the corrosion's reaction kinetics. Unknown factors and various notable factors influence the corrosion rate of a particular material in the environmental system. Significant interest in magnetic fields and their effects on electrochemical reactions have recently been gained. This paper studies the effect of an external magnetic field on the electrochemical oxidation of Aluminum (Al) in a 3,5% NaCl solution. The magnetic field 0; 0,8; 1,4; and 2,1 Tesla were used to expose the samples during corrosion testing. We found that the effect of a magnetic field on electrochemical oxidation shifts the oxidation potential to higher or lower than the oxidation potential without a magnetic field. Moreover, the oxidation potential's value depends on the magnetic field's intensity.